Changes in the posterior segment of the eye in patients with keratoconus - E. E. Ioyleva; A. Y. Safonenko (Российский офтальмологический журнал)
The literary review focuses on the studies of the posterior segment of the eye in patients with keratoconus. Anomalies in the development of the optic disk and changes in the macular area in keratoconus as well as in keratoconus combined with optic neuritis were detected using OCT, laser tomography and visual evoked potentials. The issue has not received complete solution yet. The publications are few due to the fact that it is difficult to visualize the fundus in patients with keratoconus because of high refraction errors and astigmatism of the cornea, which hampers the assessment of changes in the eye fundus. For citation: Ioyleva E.E., Safonenko A.Y. Changes in the posterior segment of the eye in patients with keratoconus. Russian ophthalmological journal. 2018; 11 (1): 99-102. doi: 10.21516/2072-0076-2018-11-1-99-102 (In Russian).